SPIRITUAL AND MORAL EDUCATION OF SCHOOLCHILDREN THROUGH ARCHITECTURAL MONUMENTS OF MIZDAKHAN - Bekniyazov Bayrambay Saparbaevich; Kudaynazarov Aydos Kengesbaevich (American Journals, 2023)
The author of the article highlights the problem of familiarizing the schoolchildren to the architectural monuments on the example of the city of Mizdakkhan for the purpose of their artistic and aesthetic education. Karakalpakstan is rich in historical and cultural heritage. The author of the article highlights the problem of familiarizing the schoolchildren to the architectural monuments on the example of the city of Mizdakxana for the purpose of their artistic and aesthetic education. The describe the practice of familiarizing to the monuments of architecture.
Keywords: Historical complex Mizdakxan, esthetics culture, personality formation, educational potential of architectural monuments, aesthetic education, schoolchildren, architecture, monuments, culture.